The lupus band test: A review of the sensitivity and specificity in the diagnosis of lupus erythematosus - Sarah Ní Maolcatha; Ellis Nic Dhonncha; Cathal O'Connor; Sinead Dinneen; Cynthia C. B. B. Heffron (Wiley, 2023)
Abstract Background The lupus band test (LBT) is a direct immunofluorescence (DIF) technique which shows a band of localised immunoglobulins at the dermo‐epidermal junction in lesional, non‐sun‐exposed skin of patients with both systemic and cutaneous lupus erythematosus (LE), and in perilesional skin of patients with systemic LE. However, low sensitivity and poor concordance between histological and clinical diagnoses warrant a review of the application of the LBT in the diagnosis of LE. Objectives To assess the sensitivity and specificity of the LBT in diagnosing LE following clinico‐pathological correlation (CPC). Methods All cases sent to our pathology department between 2011 and 2018 for DIF with a clinical query of LE were reviewed. Data collection included demographic details, pathology requests, histology and DIF reports, clinical reports and diagnoses, and serology. Results Of 256 histology requests, 9% (n = 23) had a positive LBT. This was discordant with the prevalence of LE diagnosis, as 46.3% were diagnosed with LE following CPC. The sensitivity and specificity of the LBT for LE was 17.6% and 98.8% respectively, with a positive predictive value of 92.9% and negative predictive value of 58.2%. Conclusion The LBT is not a sensitive diagnostic test for LE, but is highly specific, and should be considered as a supportive diagnostic tool for LE. This is the largest reported case series evaluating the efficacy of the LBT in the diagnosis of LE.